2005
DOI: 10.1088/1741-2560/2/1/003
|View full text |Cite
|
Sign up to set email alerts
|

Responses of rabbit retinal ganglion cells to electrical stimulation with an epiretinal electrode

Abstract: Rational selection of electrical stimulus parameters for an electronic retinal prosthesis requires knowledge of the electrophysiological responses of retinal neurons to electrical stimuli. In this study, we examined the effects of cathodal and anodal current pulses on the extracellularly recorded responses of OFF and ON rabbit retinal ganglion cells (RGCs) in an in vitro preparation. Current pulses (1 msec duration), delivered by a 125 microm electrode placed on the inner retinal surface within the receptive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
88
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 30 publications
21
88
0
Order By: Relevance
“…5). The amplitude and kinetics of the first type of response were identical to that of light-elicited action potentials, consistent with much previous work that found that short-duration pulses elicit single action potentials (Fried et al 2006;Jensen et al 2005;Sekirnjak et al 2006). The amplitude of the second type of response was considerably smaller than the standard spike (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…5). The amplitude and kinetics of the first type of response were identical to that of light-elicited action potentials, consistent with much previous work that found that short-duration pulses elicit single action potentials (Fried et al 2006;Jensen et al 2005;Sekirnjak et al 2006). The amplitude of the second type of response was considerably smaller than the standard spike (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The variability in responsiveness to pulse trains most likely arises from differences in the spike-generating machinery of each type. Almost certainly, the responses in the present study arose through direct activation of the ganglion cell: previous studies consistently indicate that pulse durations comparable to those used in our study activate ganglion cells directly without simultaneously activating presynaptic neurons (Fried et al 2006;Sekirnjak et al 2006), and also, the bursts of spiking that are characteristic of presynaptic activation (Fried et al 2006;Jensen et al 2005) were not observed in these experiments. Within the ganglion cell it is likely that spikes were initiated within the dense band of sodium channels within the axon initial segment (AIS): this region is known to have the highest sensitivity to extracellular electric stimulation (Behrend et al 2009;Fried et al 2009;Sekirnjak et al 2008), and the stimulating electrode was consistently positioned directly over its center.…”
Section: Discussionsupporting
confidence: 65%
“…However, the number of spikes increased most noticeably within about 100 ms post-stimulus. Two types of evoked RGC spikes were observed as previously reported (Jensen et al, 2005). Long-latency spikes were evoked approximately 20∼100 ms after stimulation, and could be clearly identified without contamination from a stimulation artifact.…”
Section: Characteristics Of Rgc Activitiessupporting
confidence: 71%
“…Long-latency spikes were evoked approximately 20∼100 ms after stimulation, and could be clearly identified without contamination from a stimulation artifact. These spikes are regarded as resulting from indirect stimulation of RGCs through the retinal neural network (Jensen et al, 2005). The spike waveforms in Fig.…”
Section: Characteristics Of Rgc Activitiesmentioning
confidence: 99%
“…Degenerative retinal diseases that result in the most prevalent blindness are Retinitis Pigmentosa (RP) and Age Related Macular Degeneration (AMD) [2]. Degenerative retinal diseases that lead to the most prevalent blindness are AMD and RP throughout the world and unfortunately there is no effective treatment method ranging from rebirth of photoreceptors from stem cells to neuro-protective therapy [3], [4]. Retinal Pigment Epithelium (RPE) layer of the retina are damaged by AMD.…”
Section: Introductionmentioning
confidence: 99%